2019
DOI: 10.1002/jclp.22822
|View full text |Cite
|
Sign up to set email alerts
|

Couple‐based interventions for PTSD among military veterans: An empirical review

Abstract: Objective Treatment for posttraumatic stress disorder (PTSD) is a commonly sought mental health service among military service members and veterans (SM/Vs). Such treatment is typically individually‐based, despite many SM/Vs reporting a desire for greater partner involvement in treatment. This review examined couple‐based treatments for PTSD among SM/Vs and their romantic partners. Method A database search conducted in July, 2018 yielded 167 studies, of which 16 (10%) met inclusion criteria. Brief intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 72 publications
(230 reference statements)
0
8
0
Order By: Relevance
“…Thus, in times of stress, females may feel particularly inclined to turn to their partners for support, but an increase in intimate relationship satisfaction may exacerbate stress, feelings of loneliness, and deter turning towards their partner. Finally, extant literature examining interventions to improve intimate relationship satisfaction are primarily based on samples composed of male SM/Vs and their female partners (see review, Kugler, Andresen, Bean, & Blais, 2019), thereby resulting in a gap in our knowledge about how such factors may function in females and ultimately relate to suicide risk. Further exploring this association in females could inform the development or augmentation of screening and interventions as well as determine whether sex‐specific interventions are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in times of stress, females may feel particularly inclined to turn to their partners for support, but an increase in intimate relationship satisfaction may exacerbate stress, feelings of loneliness, and deter turning towards their partner. Finally, extant literature examining interventions to improve intimate relationship satisfaction are primarily based on samples composed of male SM/Vs and their female partners (see review, Kugler, Andresen, Bean, & Blais, 2019), thereby resulting in a gap in our knowledge about how such factors may function in females and ultimately relate to suicide risk. Further exploring this association in females could inform the development or augmentation of screening and interventions as well as determine whether sex‐specific interventions are needed.…”
Section: Introductionmentioning
confidence: 99%
“…That said, several couples’ therapy interventions for SM/Vs with histories of trauma and PTSD have been shown to be effective (see review, Kugler et al., 2019). Providers treating those with histories of sexual violence experienced during military service may consider focusing on helping these individuals see their sexual dysfunction as part of the traumatic reaction, and while avoiding sexual contact may decrease painful reminders of MST (Maltz, 2002), it may also prevent survivors from experiencing safe and rewarding sexual experiences that help them heal from MST.…”
Section: Discussionmentioning
confidence: 99%
“…That said, more recent research conducted in a sample of partnered female SM/Vs observed that interpersonal traumas, such as those that included sexual violence, were associated with poorer individual and interpersonal outcomes, such as higher PTSD symptoms, lower romantic relationship satisfaction, and poorer sexual health relative to nonsexual traumas (Blais, Zalta, & Livingston, 2020; DiMauro, Renshaw, & Blais, 2018). In addition to men representing the largest cohort of military SM/Vs, the majority of these men are married (Department of Defense, 2018), and are likely to be the identified patient in couples’ therapies for PTSD (see review, Kugler, Andresen, Bean & Blais, 2019), making it is critical to expand our understanding of how unique traumas relate to interpersonal function in men SM/Vs. This information may inform the development of treatment targets and goals in couples’ therapy.…”
mentioning
confidence: 99%
“…In addition to CBT, a recent review of the literature revealed that couples' therapy was effective in simultaneously reducing posttraumatic stress disorder (PTSD) symptoms and improving relationship satisfaction among partnered SM/Vs with a history of trauma (see Kugler, Andresen, Bean, & Blais, 2019). Moreover, couples' interventions specifically aimed at treating PTSD and relationship satisfaction also effectively reduced depression symptoms and other maladaptive coping strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%